Development policies in European Union - Kisman, Zulfukar Aytac; Ventel, Annemarie (Elsevier Science Bv, 2015)
Sustainable development is a term used worldwide by politicians, even if it is a new concept. Important is that this concept is developing and defining and is continuously revised, extended and refined. Development has a positive value, so that most people would agree with, and that is associated with a better world. A change can have good parts and bad parts, and because it is difficult to reach an agreement, this may be interpreted differently from various perspectives. Sustainable development can be called fair and balanced which means to grow indefinitely, it should keep a balance between different groups of people, and from one generation to another. The main objective of applying the concept of sustainable development is to improve the quality of life and to please people. This keeps the three major interrelated areas, economic, social and environmental. Therefore, sustainable development is defined as an opportunity for a chance to prosperity, within the scope of good governance. nd to reasonable to signify sustainable development as development that can last forever or at least for a long time, for several generations. The positive side is that sustainable development is increasing and lasts for a long time. Moreover, sustainable development is increasing in consumption according to the economic interpretations. In a world where resources are limited, the main problem of the integration is to reconcile present and future needs. Two forms of distributive justice must be balanced: the inter-generational and intra-generational. The justice between generations must develop freedom and development for future generations, to evolve and to ensure options for the world's population today. (C) 2015 Published by Elsevier B.V.
International Conference on Emerging Markets Queries in Finance and Business (EMQFB) -- OCT 24-25, 2014 -- Bucharest, ROMANIA
Keywords: Development; Local Development; Development Policies; EU